"PTCH"‐ing It Together: A Basal Cell Nevus Syndrome Review. Issue 11 (31st May 2013) - Lam, Charlene; Ou, Jason C.; Billingsley, Elizabeth M.
Abstract : Background: Basal cell nevus syndrome (BCNS) has existed at least since Dynastic Egyptian times. In 1960, Gorlin and Goltz first described the classic clinical triad: multiple basal cell carcinomas (BCCs), jaw keratocysts, and bifid ribs. As an autosomal‐dominant disorder, it is characterized by tumorigenesis and developmental defects. Objective: To review the current literature on BCNS, including reports on epidemiology, pathogenesis, clinical presentation, diagnostic criteria, management, treatment, and prognosis. Methods: A literature review of currently available articles related to BCNS. Results: Individuals with a mutation in the tumor suppressor gene PTCH1 are predisposed to tumorigenesis and developmental defects. Clinical features include BCCs, often with onset in adolescence, jaw keratocysts, bifid ribs, craniofacial defects, palmar‐plantar pits, and ectopic intracranial calcification. Despite high cure rates for individual lesions and various treatment modalities including excision, Mohs micrographic surgery, photodynamic therapy, and topical imiquimod, management of BCCs is challenging. The development of an oral hedgehog pathway inhibitor, vismodegib, has added a new dimension to current treatment algorithms. Conclusions: Adolescents and young adults with BCC should be evaluated for BCNS. Early diagnosis of BCNS is critical for possible prevention of the devastating effects of BCCs and establishment of multidisciplinary care.